An Analysis of Inaugural Address of President Rodrigo Duterte’ Speech Act - Yang, Yan; Wang, Jianning (European Publisher, 2019)
Language is an important tool for the politicians to express their ideas and exert influence on the people. Politicians can fulfil many goals through the language, which includes the important speech events in campaign, election, inauguration etc. Political speech can reveal certain ideology of the speaker. Nowadays, linguistic researchers are becoming interested in this topic. While most of studies only focus on the linguistic features of the language, they do not integrate the speaker’s role in it. The present research investigates the functions of the language used by the politicians during the speech. It aims to identify and analyseze what kind of illocutionary acts mainly manifested in Rodrigo Duterte’s Inaugural Speech. Descriptive qualitative method will be adopted in this research, which is based on the Speech Act Theory. Totally, there are 75 sentences. Among which, rrepresentative utterances takes up 50.67%, Directive holds 16%, Expressive shares 13.33%, Commissive holds 13.33%, and Declarative takes up 6.67%. The result indicates Rodrigo Duterte uses more indirect speech acts than the direct one’s, which reflects his commitment to the citizen about the future of the nation. The research figures out that most utterances of Rodrigo Duterte’s speech acts are regarded as statement of fact and assertion. These speech act implies his hopes to the country’s future. It can be concluded that Rodrigo Duterte hopes that he can persuade the citizens to accept him as the president.